Impact of Supportive Resources on Middle-Aged Women's Self-Care Activities: A Study in The Vietnamese Context - Thuy Luong; Nguyen Thi Thu Ha (Asian Social Work Journal, 2021)
Addressing the fact that studies on self-care of Vietnamese middle-aged women remain scarse, our presenting study aims to investigate the relationship between supportive resources utilized by Vietnamese middle-aged women and their types of self-care. Data were collected from survey interview with 512 middle-aged women (aged from 40 to 60 years old) in Hanoi city and Quang Ninh province. A series of linear regression was performed on the six types of self-care, including: physical care, supportive relationships, mindful awareness, self-compassion & purpose, mindful relaxation, and supportive structure. Three types of supportive resources and other covariates (age, education, and residence area) were entered into these models as key predictors. The study results show that the use of different level of resources was associated with different types of self-care practice. The use of micro-resource system significantly predicted all six types of self-care among Vietnamese middle-aged women. The mesenchymal and peripheral resource systems significantly predicted physical care only among Vietnamese middled-age women. The macro resource system was significantly associated with the practice of mind-relaxing and supportive structure. In addition, people who were older, had better education and lived in urban areas tended to participate more in physical care. Women with a higher education level and living in urban areas were predicted to utilize more supportive relationships and mindful relaxation. Women living in urban areas, having a higher level of education practiced mindful relaxation significantly more than their counterparts. Using more supportive structure was significantly more among women living in urban areas, in older age groups and having higher education levels. The key findings suggest the promotion of active support from the micro-level system, as well as advocate for social policy development to help less privileged groups of women access and use mezzo and macro resources more effectively.